2020
DOI: 10.1371/journal.pone.0241834
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided internal branch of superior laryngeal nerve block on postoperative sore throat: A randomized controlled trial

Abstract: Introduction Ultrasound-guided internal branch of the upper laryngeal nerve block (USG-guided iSLN block) have been used to decrease the perioperative stress response of intubation. It is more likely to be successful than blindly administered superior laryngeal nerve blocks with fewer complications. Here, we evaluated the efficacy of USG-guided iSLN block to treat postoperative sore throat (postoperative sore throat, POST) after extubation. Methods 100 patients, aged from 18 to 60 years old, ASA I~II who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
(25 reference statements)
2
22
0
Order By: Relevance
“…Anaesthetist experience was not associated with the rate of sore throat, consistent with another study [21]. We think that tracheal intubation with smaller tubes is an easier intervention than others tested to reduce postoperative sore throat, such as drugs or laryngeal nerve block [22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 84%
“…Anaesthetist experience was not associated with the rate of sore throat, consistent with another study [21]. We think that tracheal intubation with smaller tubes is an easier intervention than others tested to reduce postoperative sore throat, such as drugs or laryngeal nerve block [22][23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 84%
“…Superior laryngeal nerve block is known to have great value in laryngopharyngeal surgery ( 22 ). Recently, it was also proven to improve POST after general anesthesia ( 23 ). In patients undergoing bronchoscopy examination, this technique could increase comfort and reduce complications, such as hypoxemia and cough ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In China, Zhipeng et al showed that Ultrasound guided SLNB might successfully decrease the postoperative sore throat after extubation under general anesthesia (13). It is noteworthy that in the present study, the reason for higher HR after the biopsy and in the recovery room in the anatomical landmark group could indicate a better block with ultrasound, but they observed sore throat after general anesthesia, and we evaluated direct laryngoscopy of the supraglottic mass.…”
Section: Discussionmentioning
confidence: 53%